2015
DOI: 10.1136/annrheumdis-2015-207315
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of disease activity in patients with rheumatoid arthritis using optical spectral transmission measurements, a non-invasive imaging technique

Abstract: ObjectivesIn rheumatoid arthritis (RA), treat-to-target strategies require instruments for valid detection of joint inflammation. Therefore, imaging modalities are increasingly used in clinical practice. Optical spectral transmission (OST) measurements are non-invasive and fast and may therefore have benefits over existing imaging modalities. We tested whether OST could measure disease activity validly in patients with RA.MethodsIn 59 patients with RA and 10 patients with arthralgia, OST, joint counts, Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 29 publications
5
36
2
Order By: Relevance
“…This confirms that OI is capable of measuring disease activity in RA at the patient level, as demonstrated in a recent study by van Onna et al 10. It may, however, not be more accurate than clinical examination at the joint level, and only after further development, it may become a useful tool for fast, physician-independent, non-invasive assessment of joint inflammation in RA.…”
supporting
confidence: 81%
“…This confirms that OI is capable of measuring disease activity in RA at the patient level, as demonstrated in a recent study by van Onna et al 10. It may, however, not be more accurate than clinical examination at the joint level, and only after further development, it may become a useful tool for fast, physician-independent, non-invasive assessment of joint inflammation in RA.…”
supporting
confidence: 81%
“…OST was found to have only moderate agreement with clinical examination, ultrasound and MRI assessments, and performed better in the proximal interphalangeal (PIP) and metacarpophalangeal (MCP) joints than the wrists. Most importantly, their results suggested that OST was a more sensitive method to detect joint areas with inflammation than clinical examination 1. However, Krabbe et al 2 did not confirm the high sensitivity of OST to detect inflammation, questioning the usefulness of the method and the validity of the results.…”
mentioning
confidence: 94%
“…Whereas FOI has been tested in a number of studies on inflammatory arthritic diseases,14–17 we have limited knowledge about the performance of the OST. Van Onna et al 1 explored the performance of OST using ultrasound and MRI as reference in patients with RA and arthralgia (controls). Patients with RA were divided into groups with increasing levels of disease activity scores (DAS28), and increasing disease activity scores were associated with higher OST values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OST and FOI have performed moderately compared to clinical examination, MRI and ultrasound in the detection of joint inflammation in patients with RA [94][95][96]. Glimm et al…”
Section: Nuclear Medicine -Spect and Petmentioning
confidence: 99%